Innovation in Large and Small Firms: An Empirical Analysis - Acs, Zoltan J.; Audretsch, David B. (American Economic Review, 1988)
[We present a model suggesting that innovative output is influenced by R&D and market structure characteristics. Based on a new and direct measure of innovation, we find that (1) the total number of innovations is negatively related to concentration and unionization, and positively related to R&D, skilled labor, and the degree to which large firms comprise the industry; and (2) these determinants have disparate effects on large and small firms.]